Thermal conductivity of polymer composites based on the length of multi-walled carbon nanotubes - Kim, Hyun Su; Jang, Ji-un; Yu, Jaesang; Kim, Seong Yun (ELSEVIER SCI LTD, 2015)
The anisotropic development of thermal conductivity in polymer composites was evaluated by measuring the isotropic, in-plane and through-plane thermal conductivities of composites containing length-adjusted short and long multi-walled CNTs (MWCNTs). The thermal conductivities of the composites were relatively low irrespective of the MWCNT length due to their high contact resistance and high interfacial resistance to polymer resins, considering the high thermal conductivity of MWCNTs. The isotropic and in-plane thermal conductivities of long-MWCNT-based composites were higher than those of short-MWCNT-based ones and the trend can accurately be calculated using the modified Mori-Tanaka theory. The in-plane thermal conductivity of composites with 2 wt% long MWCNTs was increased to 1.27 W/m.K. The length of MWCNTs in polymer composites is an important physical factor in determining the anisotropic thermal conductivity and must be considered for theoretical simulations. The thermal conductivity of MWCNT polymer composites can be effectively controlled in the processing direction by adjusting the length of the MWCNT filler. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: PHYSICAL-PROPERTIES; HEAT-FLOW; NANOCOMPOSITES; DISPERSION; FILLERS